Intravenous lacosamide in clinical practice–Results from an independent registry. (July 2016) - Lang, Nicolas; Lange, Max; Schmitt, Friedhelm C.; Bös, Monika; Weber, Yvonne; Evers, Stefan; Burghaus, Lothar; Kellinghaus, Christoph; Schubert-Bast, Susanne; Bösel, Julian; Lammers, Thorsten; Sabolek, Michael; et al.
Highlights: Intravenous lacosamide is effective and well tolerated in emergency situations with seizure activity. In 70% of patients with status epilepticus epileptic activity ceased during observation time. Caution advises to perform ECG diagnostics prior to LCM-iv administration. Abstract: Purpose: This non-interventional study was conducted to evaluate the efficacy and tolerability of intravenous lacosamide (LCM-iv) under routine conditions in daily clinical practice as a prospective registry. Methods: Patients with any type of seizure or epilepsy syndrome were recruited in 16 neurological and neuropediatric centers in Germany if the treating physician decided to administer LCM-iv for any reason. Observation time per patient was 10 days with daily documentation of LCM-iv administration, type and frequency of seizures, currently used drugs and doses, and adverse events. Treatment efficacy, tolerability, and handling of LCM-iv were assessed using a five-step scale. Results: In 119 patients treating physicians classified epilepsies as focal in 66.1% and generalized in 17.4% (16.5% unclassifiable). Most common etiologies of seizures were tumors (36.1%) and cerebrovascular diseases (21.8%). Reasons for LCM-iv treatment included preparation for surgery (25.2%), convulsive (24.4%) and non-convulsive (18.5%) status epilepticus (SE), series of seizures (16.0%), gastrointestinal causes (5.9%), and acute seizures (4.2%). The median dose of LCM-iv was 300 mg per day. In 45 of 64 patients (70.3%) with SE or series of seizures, epileptic activity ceased during observation time. Five patients showed abnormalities in ECG prior to the infusion and one patient afterwards, but during infusion no abnormalities were reported. Treating physicians rated efficacy and tolerability as very good or good in 77.6% and 93.1% of patients, respectively. Conclusions: This large and independent multicenter registry on the use of LCM-iv in clinical practice demonstrates that LCM-iv is well-tolerated and highly efficacious when given in emergency situations, including patients experiencing SE. It is advisable to perform an electrocardiogram prior to LCM-iv administration.